Taking the Gamble: Local and Regional Policy Issues of Access to Electronic Gaming Machines (EGMs): A Case Study of Victoria, Australia - Pickernell, D.; Keast, R.; Brown, Kerry; Yousefpour, N.; Miller, C. (Regional Science Association, 2013)
Gambling activities, and revenues derived, have been seen as a way to increase economic development in deprived areas. However, there are also concerns about gambling in general and Electronic Gaming Machines (EGMs) in particular, and the effects of access to these activities on the localities in which they are situated. This study explores issues of accessibility as they relate to EGM products in Victoria, focusing specifically on interactions between the location of, and demand for, EGM products. Results highlight potential twoway relationships between gambling and volunteering. Volunteering (and social capital more generally) may help protect against gambling. Alternatively and/or additionally volunteering may itself be damaged by increased gambling activity. This highlights the need for further exploration, particularly into how detrimental effects of EGMs may be mitigated in localities and beneficial impacts maximised by policy both related to the access to EGMs themselves and also the revenue and resources they generate.